Transcription of the soybean leghemoglobin genes during nodule development - Marcker, Anne (1984)
During the early stages of soybean nodule development the leghemoglobin (Lb) genes are activated sequentially in the opposite order to which they are arranged in the soybean genome. At a specific stage after the initial activation of all the Lb genes, a large increment occurs in the transcription of the Lb(c1), Lb(c3) and Lb(a) genes while the transcription of the Lb(c2) gene is not amplified to a similar extent. All the Lb genes retain significant activity for a long period during the lifetime of a nodule. Consequently the soybean Lb genes are not regulated by a developmental gene switching mechanism as is the case for vertebrate globin genes. Concomitantly with the increase in Lb gene transcription some of the other nodule specific plant genes are activated. These specific changes in the activities of the Lb and nodulin genes precede the activation of the bacterial nitrogenase gene. Thus the alteration in bacterial metabolism due to nitrogen fixation is not responsible for the observed changes in the transcriptional activities of the Lb and nodule-specific genes.